Compensation Practice in Construction Contracts Between the Government and Service Providers: a Review of the Principles of Equality and Freedom of Contract - Prajendra Wisesa, I Komang; Rohman , Adi Nur (CV. Publikasi Indonesia, 2025)
This study aims to analyze the practice of compensation in construction contracts between the government and service providers by reviewing their conformity to the principles of equality and freedom of contract. The practice of compensating in government construction projects is often colored by an imbalance of power between the parties, mainly due to the administrative dominance of the government. This study uses a qualitative approach with a case study method on the Settlement Infrastructure Supporting Special Housing for Ex-East Timorese Residents project in Kupang, East Nusa Tenggara. Data was obtained through in-depth interviews, study of contract documents, and field observations. The results of the study show that the practice of compensation does not fully reflect the principle of equality due to the weak bargaining position of service providers in the negotiation process. In addition, the principle of freedom of contract is restricted in government contracts due to strict regulations and administrative procedures. This study recommends the need to reformulate compensation clauses that are fairer and more flexible, strengthen dispute resolution mechanisms, and increase transparency and accountability in the implementation of government construction contracts.